(untitled) - Douglas Tave (Rome, 1999)
The book deals with the problem caused by unwanted imbreeding in cultured fish populations and describes management techniques that can be used to prevent or minimize inbreeding. It also describes how inbreeding can be used to improve captive populations of fish.
Keywords: fisheries - economic aspects